2018
DOI: 10.21873/anticanres.12823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D on Paclitaxel Efficacy in Triple-negative Breast Cancer Cell Lines

Abstract: The effect of vitamin D on DU4475 cell viability was different than in other TNBC cells. The effect of PTX on DU4475 cells was enhanced with vitamin D. MDA-MB-231 cells were relatively resistant to the effects of PTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Paclitaxel (PTX), a taxane, belongs to the most widely used anticancer drugs and is often applied in front-line chemotherapy in breast cancer in combination with anthracyclines or platinum chemotherapeutic drugs (reviewed in [116]). Wilhelm et al, showed that 1,25(OH)2D and 25(OH)D at low (up to 10 nM) concentrations increased the proliferation of the p53-wild type TNBC DU4475 cells and potentiated the cytotoxic action of PTX [117]. However, this effect was not observed in MDA-MB-231 cells that did not contain p53.…”
Section: Therapeutic Resistancementioning
confidence: 99%
“…Paclitaxel (PTX), a taxane, belongs to the most widely used anticancer drugs and is often applied in front-line chemotherapy in breast cancer in combination with anthracyclines or platinum chemotherapeutic drugs (reviewed in [116]). Wilhelm et al, showed that 1,25(OH)2D and 25(OH)D at low (up to 10 nM) concentrations increased the proliferation of the p53-wild type TNBC DU4475 cells and potentiated the cytotoxic action of PTX [117]. However, this effect was not observed in MDA-MB-231 cells that did not contain p53.…”
Section: Therapeutic Resistancementioning
confidence: 99%
“…One flask was used as a control group, and the other five were given docetaxel at the above concentrations. The concentrations were determined by similar corresponding experimental procedures reported in the literature [ 19 ]. The cells were then rinsed with PBS to remove dead cells, and the PBS was aspirated with a glass pipette.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, the co-treatment was more effective in ER-positive cells compared to TNBC cells. However, and very interesting, Wilhelm and colleagues showed that the effect of calcitriol or its precursor calcidiol on paclitaxel efficacy differed within the TNBC subtypes and depended on p53-positivity and VDR status [ 53 ].…”
Section: Calcitriol In Combination With Chemo/radiotherapy In Bcmentioning
confidence: 99%